2009
DOI: 10.1016/j.jenvman.2007.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Land cover mapping of wetland areas in an agricultural landscape using SAR and Landsat imagery

Abstract: 9Saline wetlands in the Monegros Desert, NE Spain, are situated in an 10 agricultural landscape which is undergoing significant changes. Agricultural 11 intensification in recent decades and current installation of new irrigation systems 12 threaten these valuable habitats, set to be included in the Natura2000 network. Their 13 preservation and successful management depend on the information available regarding 14 the transformation of surrounding areas. When soil and vegetation maps at adequate 15 scale are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 11 publications
(4 reference statements)
1
15
0
Order By: Relevance
“…These active sensors are not as sensitive to atmospheric effects, penetrate clouds, and are operational at night, thereby increasing the temporal coverage of wetland mapping. Research has shown that data from multiple sources and over multiple seasons capture greater variation in hydroperiod and vegetative condition and thus have the potential to increase both classification accuracy and confidence [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…These active sensors are not as sensitive to atmospheric effects, penetrate clouds, and are operational at night, thereby increasing the temporal coverage of wetland mapping. Research has shown that data from multiple sources and over multiple seasons capture greater variation in hydroperiod and vegetative condition and thus have the potential to increase both classification accuracy and confidence [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Wetland classification results from either multi-sensor or image fusion methods have been evaluated in the literature for tropical forested wetlands (Bwangoy et al 2010;Silva et al 2010;Rodrigues et al 2011) and grass-dominated temperate wetlands (Li and Chen 2005;Castañeda and Ducrot 2009). For tropical environments, Silva et al (2010) and Bwangoy et al (2010) reported good results using the multi-sensor method, the first studying a wetland adjacent to our study site, in the Amazon várzea, and the second mapping forested wetlands in the Congo River basin.…”
Section: Overall Classificationmentioning
confidence: 97%
“…The success of each method can likely be attributed to differences in vegetation structure and hydrological patterns among study sites, with an emphasis on achieving good results from multi-sensor classification of river floodplains. For grass-dominated temperate wetlands, however, fusionbased classification achieved the most accurate classifications, while the combination of SAR and optical data using a multi-sensor approach worsened classification accuracies (Li and Chen 2005;Castañeda and Ducrot 2009). Again, these diverging results may be linked to the different vegetation physiognomies, which will interact differently with the electromagnetic spectrum (Henderson and Lewis 2008).…”
Section: Overall Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional information provided by including an area surrounding a training point, rather than using the data from a single pixel corresponding to a training point, has been reported to increase the representativeness of the training data and improve the accuracy of the classification [34][35][36]. After trial-and-error revealed minimal sensitivity to buffer size, we used a 5 × 5 cell window at 5 m spatial resolution (approximately 12.5 m buffer radius).…”
Section: Buffer Area Training Datamentioning
confidence: 99%